2014
DOI: 10.3390/chemosensors2020097
|View full text |Cite
|
Sign up to set email alerts
|

Chemo-Electrical Signal Transduction by Using Stimuli-Responsive Polymer Gate-Modified Field Effect Transistor

Abstract: A glucose-responsive polymer brush was designed on a gold electrode and exploited as an extended gate for a field effect transistor (FET) based biosensor. A permittivity change at the gate interface due to the change in hydration upon specific binding with glucose was detectable. The rate of response was markedly enhanced compared to the previously studied cross-linked or gel-coupled electrode, owing to its kinetics involving no process of the polymer network diffusion. This finding may offer a new strategy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…This polymer on the surface was capable of undergoing a reversible glucose-dependent change in hydration at room temperature allowing the design of a gate-modified field effect transistor. 204 Zauscher and others demonstrated that poly(NIPAM)-co-poly(acrylic acid)-(3-aminophenyl-boronic acid) brushes can be used as microcantilevers for the detection of glucose at physiologically relevant concentrations. 205 Katz and others designed a signal-responsive interface by grafting poly(4-vinyl pyridine) (P4VP), functionalized with an Os-complex redox unit on the indium tin oxide surface for bioelectronic applications.…”
Section: Responsive Surfacesmentioning
confidence: 99%
“…This polymer on the surface was capable of undergoing a reversible glucose-dependent change in hydration at room temperature allowing the design of a gate-modified field effect transistor. 204 Zauscher and others demonstrated that poly(NIPAM)-co-poly(acrylic acid)-(3-aminophenyl-boronic acid) brushes can be used as microcantilevers for the detection of glucose at physiologically relevant concentrations. 205 Katz and others designed a signal-responsive interface by grafting poly(4-vinyl pyridine) (P4VP), functionalized with an Os-complex redox unit on the indium tin oxide surface for bioelectronic applications.…”
Section: Responsive Surfacesmentioning
confidence: 99%